THE ALGORITHMS OF QUASI-OPTIMAL PICTURE AREAS MATCHING - Doudkin, A. A.; Sadykhov, R. Kh.; Vatkin, M. E. (International Journal of Computing, 2014)
Using common matching quality criteria the problem of optimum matching of partially overlapped picture areas is considered. Two schemes of algorithms are proposed for quasi-optimal solution of the problem with following restrictions: the areas are rectangular and have an identical scale. In the first scheme local criterion is used to estimate a quads of frames located in square matrix. In the second scheme is used the special distance function based on neighbor picture matching criterion. The algorithms are realized in program system of layout metallization restoring of integrated circuits.